Custo-efetividade de antipsicóticos atípicos para o tratamento da esquizofrenia - Santos, André; Vidal, Carlos Eduardo; Brandão, Cristina (Jornal Brasileiro de Economia da Saúde, 2016)
Objectives: To conduct a cost-effectiveness analysis of second-generation antipsychotics (SGA) for schizophrenia in Brazil. Methods: A Markov model was built for the evaluation of the cost-effectiveness of risperidone, quetiapine, ziprasidone and olanzapine in the Brazilian public health system. The time horizon of the analysis was 18 months. The effectiveness was measured in terms of discontinuation of treatment for any cause and the costs were measured in 2014 BRL and USD. Results: Olanzapine was found to be dominant over the other strategies. The analysis of the optimal choice indicated that olanzapine was recommended, considering a null Willingness-to-Pay (WTP), in 51.8% of the trials. The increase in values of WTP makes the chance of olanzapine to be optimal increase, achieving 100% at approximately 252.00 BRL (114.03 USD) per month of effective treatment. The Probabilistic Sensitivity Analysis (PSA), has shown olanzapine to be optimal in 49.6% of the trials, considering a null WTP. The chance of optimality of olanzapine achieved 100% at a WTP of 364,00 BRL (164.71 USD) per month of effective treatment. The results have shown the importance of prescription costs of olanzapine and hospitalization costs for the Incremental Cost-Effectiveness Ratio (ICER). Conclusion: Olanzapine was found to be dominant over risperidone, quetiapine and ziprasidone, in Brazil. The sensitivity analysis has shown that the cost-effectiveness relationship between olanzapine and risperidone can be modified by the price of purchase of olanzapine. Due to the low values of ICER showed in the sensitivity analysis and PSA, olanzapine can be considered the most cost-effective strategy evaluated.